Quantification of Elastin, Collagen and Advanced Glycation End Products as Functions of Age and Hypertension - Atanasova, Milena; Dimitrova, Aneliya; Ruseva, Boryana; Stoyanova, Angelina; Georgieva, Miglena; Konova, Emiliana (IntechOpen, 2012)
None